SnO2 Extended Gate Field-Effect Transistor as pH Sensor - P. D. Batista (Brazilian Journal of Physics, 2006)
Extended gate field-effect transistor (EGFET) is a device composed of a conventional ion-sensitive electrodeand a MOSFET device, which can be applied to the measurement of ion content in a solution. This structurehas a lot of advantages as compared to the Ion- Sensitive Field Effect Transistor (ISFET). In this work, weconstructed an EGFET by connecting the sensing structure fabricated with SnO2 to a commercial MOSFET(CD4007UB). From the numerical simulation of site binding model it is possible to determine some of thedesirable characteristics of the films. We investigate and compare SnO2 films prepared using both the Sol-geland the Pechini methods. The aim is an amorphous material for the EGFET. The SnO2 powder was obtained atdifferent calcinating temperatures (200 - 5000C) and they were investigated by X-ray diffraction (XRD), infraredspectroscopy (IR), thermogravimetric analysis (TGA) and differential thermal analysis (DTA). The films wereinvestigated as pH sensors (range 2-11).